In situ effects of biochar on aggregation, water retention and porosity in light-textured tropical soils - Obia, Alfred; Mulder, Jan; Martinsen, Vegard; Cornelissen, Gerard; Børresen, Trond (Soil and Tillage Research, 2016)
Biochar (BC) has been reported to improve soil physical properties mainly in laboratory and greenhouse pot experiments. Here we study, under field conditions, the effect of BC and its particle sizes on soil aggregate stability, bulk density (BD), water retention, and pore size distribution in two experiments in Zambia. A) Farmer practice experiment in sandy loam with maize cob BC in conservation farming planting basins under maize and soybeans crops. B) Maize cob and rice husk BC particle size experiments ( 0.5, 0.5–1 and 1–5 mm particle sizes) in loamy sand and sand. In the farmer practice experiment, BC increased aggregate stability by 7–9% and 17–20% per percent BC added under maize and soybeans crops respectively (p < 0.05) after two growing seasons. Total porosity and available water capacity (AWC) increased by 2 and 3% respectively per percent BC added (p < 0.05) under both crops, whereas BD decreased by 3–5% per percent BC added (p 0.01). In the maize cob BC particle size experiment after one growing season, dose was a more important factor than particle size across the soils tested. Particle size of BC was more important in loamy sand than in sand, with 0.5 and 1–5 mm sizes producing the strongest effects on the measured properties. For example, BD decreased while total porosity increased (p < 0.01) for all BC particle sizes in sand whereas only 1–5 mm BC significantly decreased BD and increased total porosity in loamy sand (p < 0.05). However, AWC was significantly increased by only 0.5 and 1–5 mm BCs by 7–9% per percent BC added in both loamy sand and sand. Rice husk BC effect after one year followed similar pattern as maize cob BC but less effective in affecting soil physical properties. Overall, reduced density of soil due to BC-induced soil aggregation may aid root growth and with more water available, can increase crop growth and yields.
Keywords: Biochar particle size; Soil aggregate; stability Soil; water retention